Experimental study on effect of injection retard on emissions and performance in a diesel engines - Pourdarbani, Razieh (International Journal of Engineering and Technology, 2018)
In this research, engine OM 364 LA, made in IDEM Co. was studied. Engine emissions include CO, NOx and UHC were tested using ISIRI 6764 standard (ECE-R49) and ESC test cycle. The test cycle consisted of 13 steady states in the different range of rpm and loads (25 to 100 %). the goal was experimentally study on the effects of injection retard on NOx emissions and engine performance. The results indi-cated a 65% reduction in NOx emissions but at the cost of a 14% reduction in engine power. Although the overall results indicate a drop in performance and a reduction in engine thermal efficiency due to injection retard but in contrast, there is a significant improvement and reduc-tion of NOx emission. Â